2018
DOI: 10.1016/j.anorl.2017.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Semilunar conchal cartilage graft in saddle nose reconstruction

Abstract: This modified conchal cartilage graft presents itself as an excellent reconstructive option, especially considering its low morbidity, availability and ability to retrieve an adequate amount of cartilage in the vast majority of patients. These modifications of the conchal cartilage are previously unreported, and provide the needed height and elasticity in saddle nose reconstruction without the need for additional grafting. It is important to stress that when positioned properly, a beneficial effect in peak nas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Since the first attempt in 1887 by Roe, 15 plastic surgeons kept on chasing ideal substitutes for the reconstruction of nasal framework. Till now, a varies of autologous approaches have been carried out including septal cartilage graft, costal cartilage graft and conchal cartilage graft et al 4,16,17 Despite that autologous tissue graft is considered as a preferred option for its superior biocompatibility when compared to alloplastic implants, the utilization of autologous cartilage is still highly restricted in most Asian patients. On one hand, East Asian populations tend to have weaker framework and hypogenetic septal cartilage when compared to Caucasians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first attempt in 1887 by Roe, 15 plastic surgeons kept on chasing ideal substitutes for the reconstruction of nasal framework. Till now, a varies of autologous approaches have been carried out including septal cartilage graft, costal cartilage graft and conchal cartilage graft et al 4,16,17 Despite that autologous tissue graft is considered as a preferred option for its superior biocompatibility when compared to alloplastic implants, the utilization of autologous cartilage is still highly restricted in most Asian patients. On one hand, East Asian populations tend to have weaker framework and hypogenetic septal cartilage when compared to Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…Rhinoplasty surgery stands as the most effective intervention. Rašić 4 introduced a modified semilunar conchal cartilage graft and Haack 5 illustrated that split calvarial bone L-shaped strut was also feasible. Chen et al 6 indicated the utilization of remaining septal cartilage strips or costal cartilage from 6th or 7th rib in all their 4 types of septal reconstruction methods.…”
mentioning
confidence: 99%
“…The options for grafting may be constrained if using ear cartilage, however, a butterfly graft may be a useful reconstructive technique for milder cases. 14,15 Septal cartilage is usually impractical in these patients because they almost always have a preexisting deficiency, most commonly from a perforation. Irradiated homograft costal cartilage may be used and has been shown to have long-lasting results.…”
Section: Management Of the Caudal Septummentioning
confidence: 99%
“…The involvement of the internal nasal valve (INV), if not adequately reconstructed, is often associated with an alteration of inspiratory/expiratory flows, secondary to INV collapse. Several reconstructive methods have been described: upper lateral Strut graft, 1 alar batten graft, 2 semilunar conchal cartilage graft, 3 and auricular chondrocutaneous composite graft. 4 Additionally, some literature reviews reveal the significant role of chondrocutaneous graft in nasal reconstruction.…”
Section: Introductionmentioning
confidence: 99%